Analysis of CO2 and CH4 Emission from Domestic Waste in Open Space Bendan Dhuwur Campus UPGRIS Semarang - Nindita, Velma; Widiastuti, Kurnia; Supriyadi, Slamet (Science and Technology Research Centre, Universitas PGRI Semarang, 2022)
Various activities especially in fulfillment daily needs, generate a lot of waste. One of the negative effects of waste generation is the contribution of greenhouse gas emissions to the atmosphere which causes global warming. Every location has waste, both organic and non-organic, or other types. The open space in Bendan Dhuwur campus area is dominated by organic waste due to leaf fall from many trees around. This is a concern because there is no proper waste management and it is immediately burned. This study focuses on analyzing the composition of waste and calculating the contribution of CO2 emissions from domestic waste generation at Bendan dhuwur campus of UPGRIS Semarang. The method used is random sampling accompanied by quantitative descriptive measurements and analysis. The result of the research shows that the calculation of waste composition for leaf waste is 3.58 x 10-3 Gg/year; twig waste 3.6 x 10-4 Gg/year; paper waste 3.57 x 10-4 Gg/year; plastic waste 2.02 x 10-4 Gg/year and CO2 emissions = 2.12 x 10-3 Gg/year; CH4= 2.57 x 10-5 Gg/year (leaves), CO2 = 2.18 x 10-4 Gg/year; CH4=2.58 x 10-6 Gg/year (twig), CO2 = 1.53 x 10-4 Gg/year; CH4= 2.56 x 10-6 Gg/year (paper), CO2 = 0.02 Gg/year; CH4= 1.45 x 10-6 Gg/year (plastic) Keywords: waste, CO2, CH4